Effect of Intra-Stromal Bevacizumab on Corneal Vascularization: 10.36351/pjo.v39i1.1550 - Niazi, Muhammad Khizar; Masood, Hifza; Ali, Kashif; Malik, Saad Mushtaq; Arshad, Muhammad Asharib (Pakistan Journal of Ophthalmology, 2022)
Purpose: To study the effect of Intra-stromal Bevacizumab on corneal vascularization. Study Design: Quasi experimental study. Place and Duration of Study: Outpatient department of the Combined Military Hospital, Multan from April 2022 to August 2022. Methods: Thirty patients were recruited through non-probability, convenience sampling technique. Ethical approval was taken from Institutional Review Board. Complete ocular examination was performed by a consultant ophthalmologist and patients with corneal neovascularization were included in the study. Area of corneal vascularization was measured on slit lamp. After taking all the aseptic measures and administering anesthetic eye drops, patients were administered 0.2 ml of (2.5 mg/0.1 mL) Bevacizumab (Avastin, Roche) using an ophthalmic microscope. The patient was then called for a follow up after 4 weeks and then the grade of corneal vascularization was checked by a consultant ophthalmologist on slit lamp examination. Data analysis was doneusing SPSS version 25. Results: Mean age of the patients was 43.4 ± 13.7 years (range 25 to 72 years). Male to female ratio was 2:3. There was significant decrease in the area of corneal neovascularization from 2.78mm ± 0.30 to 2.50mm ± 0.27 (p = 0.0003). The mean change in the area of corneal neovascularization was 10.07%. Two patients had sub-conjunctival hemorrhage which settled over due course of time. Conclusion: Intra-stromal Bevacizumab resulted in significant reduction in vascularized area of cornea with minimal side effects indicating that intra-stromal Bevacizumab is an effective and safe modality in the treatment of corneal neovascularization.